Use of the ProKnow-c tool in the study of the development of the brazilian railway mode - Lima, Beatriz Alves; Ferreira, Jaiane dos Santos; Santos, Joice Vieira dos; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2024)
In the scenario of rapid changes driven by technological advances, logistics has played a fundamental role, enabling the efficient transport of goods and people. This article seeks to carry out a literature review using the ProKnow-C methodology, research systematization and article selection, to obtain a qualitative analysis and a significant bibliographic portfolio regarding the railway modality in Brazil. To select the articles, after defining the key words, a search was carried out in 4 journals to select the raw article bank. The research took place selecting 365 works from 2010. Then, 6 filtering phases were applied to select articles aligned with the proposed theme, thus reaching a final quantity of 16 articles. The analyzes showed that the railway theme was studied over the years 2010 to 2023, there are relevant studies on the sector, the search for new approaches to the topic and the existence of researchers dedicated to the area. It can be concluded that the study was successful in achieving the established objectives.